Le marché immobilier à Montréal en 1981 - Daigneault, André (Assurances, 1982)
The steep rise in mortgage interest rates has placed the real estate borrower in rather difficult straits. Similarly, the extremely high cost of materials, labour and money has slowed down construction starts to such an extent that the number of dwellings now available has dropped to a dangerously low level. Moreover, interference from the Quebec Rent Board has to this day prevented any levelling out of supply and demand. In his article, the author studies both the financial and social implications of this doubly troublesome situation.